1967
DOI: 10.1111/j.1749-6632.1967.tb27720.x
|View full text |Cite
|
Sign up to set email alerts
|

The Results of Some Comparative Experimental Investigations of L‐forms of Bacteria and Mycoplasma*

Abstract: It is well known that the differentiation of mycoplasma and L-forms of bacteria is very difficult because of their biological similarity. Therefore, the aim of our investigations was to find possible criteria for differentiating between these microorganisms. Hence, we conducted the following comparative investigations of the morphology of L-forms of bacteria and mycoplasma, their antigenic peculiarities, behavior in tissue cultures and their capacity to produce a certain pathogenic effect in experimental infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1969
1969
1975
1975

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The mycoplasmainfected cells were also less sensitive to exogenously supplied interferon. However, other investigators have found some suggestion of increased production of interferon when mycoplasma and virus are present together (25,88,205).…”
Section: Suppression Of Rous-associated 'Virus (Rav) Wasmentioning
confidence: 99%
See 2 more Smart Citations
“…The mycoplasmainfected cells were also less sensitive to exogenously supplied interferon. However, other investigators have found some suggestion of increased production of interferon when mycoplasma and virus are present together (25,88,205).…”
Section: Suppression Of Rous-associated 'Virus (Rav) Wasmentioning
confidence: 99%
“…The effects of mycoplasmas on the morphology of contaminated cell lines range from zero (26,135,155,156) to increase in cytoplasmic granularity and retardation of growth (91,185,186) to frank cytopathology (3,9,24,27,54,61,66,76,84,88,137,185,186). The mycoplasmas may have such a drastic effect upon the cell cultures that the whole cell population lyses (92, 94).…”
Section: Mycoplasma Effects On Cell Growth and Morphology Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that mycoplasmas may enhance (43), depress (36), or have no effect on (2) the induction of interferon by various agents in tissue culture. Similar diverse effects of mycoplasmas on viral replication are well documented (2,16,24,36). The ability of A. Iaidlawii to induce interferon in mammalian cells should be viewed with some concern due to increasing frequency of isolation of this and other mycoplasmal species from cell cultures (18,38).…”
Section: Min (V) Activity Against Both Vsv and Sindbis Viruses In Flmentioning
confidence: 79%
“…As with A. laidlawii, BTV elicited higher levels of interferon in leukocytes from ewe #7 than in cell cultures from ewe #46. The interferon induced by A. Iaidlawii was usually not detectable until 48 h postinoculation, whereas that induced by BTV was apparent at 24 h.…”
Section: Downloaded Frommentioning
confidence: 97%